2020
DOI: 10.3126/jpan.v9i1.31308
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-behavioural impact of ‘Lockdown’ due to COVID-19 pandemic in Nepal: An Online Survey

Abstract: Introduction: Nepal entered into a lockdown mode since 24th March 2020 to control the spread of COVID-19 infection. Our aim was to evaluate the mental and behavioural impact of lockdown due to COVID-19 pandemic on the general public of Nepal in terms of the point prevalence of sadness, anxiety, feelings and relationship issues due to lockdown. Material And Method: It was a web-based cross-sectional survey conducted by using the Survey Monkey platform during 8th April 2020 and 29th April 2020. The link ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The prevalence of anxiety is in line with the study done by Gupta et al which showed 25.4% but the prevalence is higher in our sample as compared to 7% 21 but comparable to another study by the same author. 23 Also, our data is well within the range suggested by a recent meta-analysis among the general population during the COVID-19 pandemic in China, Spain, Italy, Iran, the US, Turkey, Nepal, and Denmark i.e. the rates of symptoms of anxiety 6.33% to 50.9%, depression:14.6% to 48.3%, and stress: 8.1% to 81.9%.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of anxiety is in line with the study done by Gupta et al which showed 25.4% but the prevalence is higher in our sample as compared to 7% 21 but comparable to another study by the same author. 23 Also, our data is well within the range suggested by a recent meta-analysis among the general population during the COVID-19 pandemic in China, Spain, Italy, Iran, the US, Turkey, Nepal, and Denmark i.e. the rates of symptoms of anxiety 6.33% to 50.9%, depression:14.6% to 48.3%, and stress: 8.1% to 81.9%.…”
Section: Discussionsupporting
confidence: 88%